FACTORS AFFECTING NON-MUSLIM STUDENTS OF FACULTY OF HUMANITIES OF UNIVERSITAS INDONESIA TOWARDS ARABIC - Manurung, Catherine; Letmiros, Letmiros (UI Scholars Hub, 2023)
Arabic is a foreign language commonly spoken by many people all over the world; moreover, internationally, it plays such a strategic role. Nevertheless, Indonesian non-Muslims have a relatively low interest in Arabic. We can observe it from the relatively low number of non-Muslims who major in Arabic literature in various universities all over Indonesia. Therefore, this is such an interesting phenomenon to be studied. We think that this phenomenon takes place due to their inappropriate or incorrect perceptions towards Arabic. This study is aimed at identifying various factors affecting the perception of non-Muslim students of Faculty of Humanities of Universitas Indonesia (FIB-UI) in the Class of 2020 towards Arabic. This study employs a quantitative method with a descriptive approach. The participants in this study are non-Muslim students of Faculty of Cultural Sciences of Universitas Indonesia (FIB-UI) in the Class of 2020 with the samples amounting to 53 persons. To process the data of the study, we employ an exploratory factor analysis method. Based on the results of the study, it is found out that there are 5 factors affecting their perceptions such as the introduction factor, the Arabic characteristic factor, the assessment/assumption factor, the language-as-a-religious-identity factor, and the stereotypes-of-the-Muslims factor.